Simulation Study of the Interaction between Respiration and the Cardiovascular System - Bai, Jing; Lu, Hongli; Zhang, Jupeng; Zhou, Xiaoqiang (Methods of Information in Medicine, 1997)
Many studies have been done on the respiratory and the cardiovascular system. Among them, only a few are on the interaction of these two physiologic systems. To explore the mechanism of the integration of these two physiological systems, computer simulation has been done; we report the preliminary results obtained in our laboratory. In this study, a mathematical model of the cardiovascular system integrated with the respiratory mechanical system has been established. The model is based on our previous work on cardiovascular modeling. The previous lumped lungi model has been replaced by a multielement model with more detail. Inter- thoracic and abdominal pressures are modeled as external pressure sources on the related cardiovascular elements. Using this model, a sequence of simulation studies have been carried out. Different respiratory modes have been simulated and the different effects are observed in the simulation results. The results indicate that by following a certain respiratory pattern, the circulation status can be improved. These results agree with clinical observations.Keywords: Mathematical Model, Respiration Mode, Cardiovascular System, Computer Simulation, Interaction
Keywords: Mathematical Model; Respiration Mode; Cardiovascular System; Computer Simulation; Interaction